Iron-based flow battery negative electrode electrolyte and preparation method thereof
By using specific chelating agents to form stable complexes with iron ions in iron-based flow batteries, the problems of poor energy density and reaction speed of existing iron-based flow batteries are solved, and higher battery performance and stability are achieved , suitable for large-scale and small-scale energy storage equipment.
Patent Information
- Application Number
- CN202411338106.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-24
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-09-24
AI Technical Summary
The energy density, reaction speed and safety and stability of existing iron-based flow batteries are poor, which limits their application in the field of energy storage.
By adding specific chelating agents to the negative electrode electrolyte of the iron-based flow battery, such as tris(hydroxymethyl)methylglycine, N,N-bis(2-hydroxyethyl)glycine and N-(2-hydroxyethyl)glycine to the negative electrode electrolyte of the iron-based flow battery, )iminodiacetic acid forms a stable complex with iron ions, improves its solubility and chemical stability, and prepares a variety of new iron-based liquid flow battery selection solutions.
It improves the energy density and reaction speed of the battery, increases the potential difference of the single cell, provides faster charging and discharging capabilities and higher stability, reduces the cost of electrolyte, and is suitable for applications of large-scale and small-scale energy storage equipment.
Smart Images

Figure HDA0005058860530000011 
Figure HDA0005058860530000012 
Figure HDA0005058860530000021
Abstract
Description
Technical Field
[0001] The present invention relates to the field of liquid flow battery energy storage technology, specifically an iron-based liquid flow battery negative electrode electrolyte and a preparation method thereof, which can be used in solar energy and wind energy power generation systems as large-scale electric energy storage and high-efficiency conversion equipment, and also has broad application prospects in small energy storage equipment such as automotive batteries and household energy storage. Background Art
[0002] With the rapid development of our society and the rapid growth of our economy, we are also facing a huge price - a surge in energy consumption and serious environmental pollution. Therefore, in order to resolve the contradiction between man and nature, clean and renewable energy (such as wind and solar energy) is widely used. However, these energy sources usually have problems of discontinuity and instability, so energy storage facilities are required during use. Iron-based flow batteries are expected to be used as large-scale or distributed energy storage systems in power facilities due to their high safety, low cost and high power density, promoting the efficient use of clean and renewable energy.
[0003] The structure of a flow battery is mainly composed of a liquid storage tank, a battery stack, and a pump. When the battery is running, the pump injects the electrolyte of the positive and negative electrodes from the liquid storage tank into the battery, flows through the surface of the positive and negative electrodes, and an electrochemical reaction occurs. The positive and negative electrolytes are separated by an ion-selective permeable membrane. The positive and negative electrodes are connected to the power load and transfer electrons through the circuit, while the positive and negative ions are transferred through the diaphragm inside the battery to form a complete current loop.
[0004] At present, commercialized all-vanadium flow batteries have shown their advantages in the field of energy storage, but from the perspective of long-term development, they still have some shortcomings in resource utilization, environmental protection and cost control. Iron-based flow batteries have multiple advantages over all-vanadium flow batteries. First, the iron material used in iron-based batteries is of lower cost, while the vanadium material of all-vanadium batteries is of higher price, so they have more advantages in initial investment and operating costs. In addition, iron is one of the most abundant elements on earth, and its resources are relatively easy to obtain, while vanadium resources are relatively scarce and may face supply chain risks. The materials of iron-based flow batteries have less impact on the environment and meet the requirements of sustainable development, while the mining and processing of vanadium may have a certain impact on the environment. In terms of safety, iron-based batteries are safer during use, less prone to fire or explosion, and suitable for large-scale applications. At the same time, iron-based flow batteries show good cycle stability during multiple charge and discharge processes, which is suitable for long-term energy storage needs. In addition, its design and manufacturing are relatively simple, which may reduce the complexity and maintenance costs of the system. These advantages make iron-based flow batteries a more attractive option than all-vanadium flow batteries in some application scenarios, especially in terms of cost and resource sustainability. Summary of the invention
[0005] The purpose of the present invention is to improve the shortcomings of existing iron-based liquid flow batteries, overcome the problems of poor energy density, reaction speed and safety and stability of electrolytes, enrich the formula of negative electrode electrolytes of iron-based liquid flow batteries, and provide a variety of new iron-based liquid flow battery options. The chelating agent in the present invention forms a stable chelate with iron ions, has high solubility, good thermal stability and chemical stability, and is suitable for use under various conditions.
[0006] The technical solution for achieving the purpose of the present invention is:
[0007] An iron-based liquid flow battery negative electrode electrolyte and a preparation method thereof, characterized in that the negative electrode electrolyte comprises an active substance, a ligand, a supporting electrolyte, and an auxiliary electrolyte; the active substance is one or more of ferric sulfate, ferric nitrate, ferric chloride, and ferric acetate; the ligand is one or more of tris(hydroxymethyl)methylglycine, N,N-bis(2-hydroxyethyl)glycine, and N-(2-hydroxyethyl)iminodiacetic acid; the supporting electrolyte is one or more of sodium hydroxide, potassium hydroxide, lithium hydroxide, potassium carbonate, sodium carbonate, and lithium carbonate; the auxiliary electrolyte is one or more of potassium chloride, potassium nitrate, sodium nitrate, sodium chloride, ammonium chloride, potassium sulfate, sodium sulfate, and ammonium sulfate; and the solvent is oxygen-free deionized water.
[0008] Further, when the ligand is tri(hydroxymethyl)methylglycine, the corresponding supporting electrolyte is one or more of sodium hydroxide, potassium hydroxide, and lithium hydroxide; when the ligand is N,N-bis(2-hydroxyethyl)glycine or / and N-(2-hydroxyethyl)iminodiacetic acid, the corresponding supporting electrolyte is one or more of potassium carbonate, sodium carbonate, and lithium carbonate.
[0009] The molar ratio of the ligand to the iron ions in the active substance is 5:1 to 2:1, and the preferred ratio is 3:1.
[0010] Furthermore, the molar concentration of iron ions in the active substance is 0 to 1.2 mol / L and is not 0, preferably 0.1 to 0.6 mol / L; the molar concentration of the ligands tri(hydroxymethyl)methylglycine, N,N-bis(2-hydroxyethyl)glycine, and N-(2-hydroxyethyl)iminodiacetic acid is 0 to 5.0 mol / L and is not 0, preferably 0.5 to 2.5 mol / L; the molar concentration of the supporting electrolyte is 0 to 8.0 mol / L, preferably 1.0 to 4.0 mol / L; the molar concentration of the auxiliary electrolyte is 0 to 3.0 mol / L, preferably 0.2 to 1.5 mol / L.
[0011] An iron-based liquid flow battery negative electrode electrolyte and a preparation method thereof, characterized in that the preparation process of the negative electrode electrolyte is as follows:
[0012] (1) introducing an inert gas into the reactor to exhaust the air;
[0013] (2) adding active substances, ligands, and auxiliary electrolytes, mixing, adding deionized water, and stirring for 1 to 3 hours;
[0014] (3) Then add the supporting electrolyte and stir thoroughly for 1 to 3 hours to make a uniform solution.
[0015] After standing for 6 hours, use it, test the pH and viscosity and record them.
[0016] An iron-based liquid flow battery, comprising a positive electrode, a negative electrode, positive and negative electrolytes, a diaphragm and a battery housing, wherein the positive electrode, the negative electrode, the positive and negative electrolytes and the diaphragm are contained in the battery housing, the diaphragm is located between adjacent positive and negative electrodes, and both sides of the diaphragm are in contact with the positive and negative electrolytes. The negative electrode electrolyte is the negative electrode electrolyte of the present invention;
[0017] Furthermore, the positive electrode electrolyte is potassium ferrocyanide, an auxiliary electrolyte and / or a supporting electrolyte having the same anion as the supporting electrolyte of the corresponding negative electrode electrolyte.
[0018] Furthermore, the positive electrode or the negative electrode is a porous carbon material electrode.
[0019] Furthermore, the diaphragm is a Nafion membrane with a thickness of 50 to 200 μm.
[0020] Furthermore, the operating temperature of the negative electrode electrolyte is 10 to 70°C.
[0021] Compared with the prior art, the present invention has the following significant advantages and beneficial effects:
[0022] 1. The present invention improves the formula of the negative electrode electrolyte of the iron-based liquid flow battery by adding tris(hydroxymethyl)methylglycine, N,N-bis(2-hydroxyethyl)glycine, N-(2-hydroxyethyl)iminodiacetic acid or its chemical derivatives to form a complex with iron salts, and provides a variety of new iron-based liquid flow battery options. Tris(hydroxymethyl)methylglycine can be used with strong alkaline electrolytes, and N,N-bis(2-hydroxyethyl)glycine and N-(2-hydroxyethyl)iminodiacetic acid can be used with weak alkaline electrolytes. They can be used with positive electrode electrolytes in neutral, weak alkaline, and strong alkaline environments to assemble different batteries. And compared with other carboxylic acid ligands, the voltage window of tris(hydroxymethyl)methylglycine to form a complex is further shifted to the negative side, increasing the potential difference of the single cell, thereby improving the energy density.
[0023] 2. The chelating agent used in the present invention has a central nitrogen atom connected to a variety of hydroxyl or carboxyl functional groups, and the solubility of the formed complex is high, the concentration of active substances for redox in the electrolyte is increased, and the energy density is improved. The electrolyte can also provide fast charge and discharge capabilities at a higher current density and quickly respond to changes in power demand.
[0024] 3. The chelating agent selected in the present invention is inexpensive, the electrolyte cost is low, safe and stable, and the electrolyte preparation method is simple and easy to scale up. It can be used not only in large-scale electric energy storage and high-efficiency conversion equipment, but also in small energy storage equipment such as automotive batteries and household energy storage. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 For Example 1, 10 to 100 mV·s -1 Cyclic voltammetry curves inside.
[0026] Figure 2 For Example 2, 10 to 50 mV·s -1 Cyclic voltammetry curves inside.
[0027] Figure 3 For Example 3, 10 to 50 mV·s -1 Cyclic voltammetry curves inside.
[0028] Figure 4 The charge and discharge efficiency and capacity-cycle curves within 280 cycles of Example 1 are shown.
[0029] Figure 5 The charge and discharge efficiency and capacity-cycle curves within 70 cycles of Example 2 are shown.
[0030] Figure 6 The charge and discharge efficiency and capacity-cycle curves within 90 cycles of Example 3. DETAILED DESCRIPTION
[0031] The present invention is described in detail below through specific examples, but the use and purpose of these exemplary embodiments are only used to illustrate the present invention, and do not constitute any form of limitation on the actual protection scope of the present invention, nor limit the protection scope of the present invention to these.
[0032] Embodiment 1:
[0033] In this embodiment, the main components of the negative electrode electrolyte include: ferric chloride, tris(hydroxymethyl)methylglycine as a complex, sodium hydroxide as a supporting electrolyte, potassium chloride as an auxiliary electrolyte, and oxygen-free deionized water as a solvent. Among them, the concentration of ferric chloride is 0.2 mol / L, the concentration of tris(hydroxymethyl)methylglycine is 0.8 mol / L, the concentration of sodium hydroxide is 1.6 mol / L, and the concentration of potassium chloride is 0.2 mol / L.
[0034] The specific steps for preparing the negative electrode electrolyte are as follows:
[0035] Nitrogen was introduced into the reactor to exhaust the air, and 5.4 g of ferric chloride, 14.3 g of tris(hydroxymethyl)methylglycine, 6.4 g of sodium hydroxide, and 1.5 g of potassium chloride were added in sequence. After mixing, deionized water was added and stirred for 8 hours to make a uniform solution. The solution was fixed to 100 mL and allowed to stand for 12 hours before use.
[0036] The above negative electrode electrolyte was subjected to electrochemical testing, and the results are as follows: Figure 1 As shown. In 2~100mV·s -1 The scan rate and current density of the cyclic voltammetry curve show a regular linear relationship, and the redox current intensity is similar, which has good reversibility. In carboxylic acid ligands, the voltage window can move to a lower voltage (more negative potential), and the reduction peak potential is after -1.0V, increasing the potential difference of the single cell.
[0037] In the battery test, the positive electrode electrolyte used 0.5 mol / L potassium ferrocyanide and 0.5 mol / L potassium hydroxide electrolyte.
[0038] Add the positive and negative electrolytes to the corresponding liquid storage tanks of the liquid flow battery. The liquid flow battery system mainly consists of batteries, positive and negative liquid storage tanks, positive and negative peristaltic pumps, corrosion-resistant circulation pipelines, and battery testing systems. The battery components include: aluminum end plates, polytetrafluoroethylene gaskets, collector plates, graphite bipolar plates, fluororubber gaskets, proton exchange membranes, and graphite felt electrodes. The graphite felt electrode is 3cm×3cm, and the proton exchange membrane is a Nafion 117 membrane.
[0039] After the above components are assembled, inert gas is first circulated in the battery system to prevent the active substances from being deactivated, and then the battery test system is connected to start the test. The volume of the positive and negative electrolytes is 10 ml each, and the positive and negative electrodes are 3×3 cm 2 Porous carbon felt electrode, proton membrane is Nafion 117 membrane.
[0040] At a higher current density of 80 mA / cm 2 The battery was charged to 1.8 V at a higher current density of 80 mA / cm 2 The assembled iron-based flow battery was subjected to 280 charge and discharge cycle tests. The charge and discharge efficiency and capacity-cycle curves within 280 cycles are shown in Figure 2. Figure 4 Under the above high current density conditions, within 280 cycles, the coulombic efficiency (CE) is about 90%, the energy efficiency (EE) and the voltage efficiency (VE) are about 60% and 70% respectively, with good stability and slow charge and discharge capacity decay.
[0041] Embodiment 2:
[0042] In this embodiment, the main components of the negative electrode electrolyte include: ferric nitrate, N, N-bis (2-hydroxyethyl) glycine as a complex, potassium carbonate as a supporting electrolyte, sodium chloride as an auxiliary electrolyte, and oxygen-free deionized water as a solvent. Among them, the concentration of ferric nitrate is 0.2 mol / L, the concentration of N, N-bis (2-hydroxyethyl) glycine is 0.8 mol / L, the concentration of potassium carbonate is 1.2 mol / L, and the concentration of sodium chloride is 0.2 mol / L.
[0043] The specific steps for preparing the negative electrode electrolyte are as follows:
[0044] Nitrogen was introduced into the reactor to exhaust the air, and 8.1 g of ferric nitrate, 13.1 g of N, N-bis(2-hydroxyethyl)glycine, 16.6 g of potassium carbonate, and 1.2 g of sodium chloride were added in sequence. After mixing, deionized water was added and stirred for 24 hours to make a uniform solution. The solution was fixed to 100 mL and allowed to stand for 12 hours before use.
[0045] The electrolyte of the positive electrode is mainly 0.4 mol / L sodium ferrocyanide and 0.4 mol / L sodium chloride electrolyte.
[0046] After the battery system is assembled, other reference conditions are the same as in Example 1.
[0047] Connect to the battery test system and start the test. The volume of the positive and negative electrolytes is 20 ml each, and the positive and negative electrodes are 3×3 cm 2 The porous carbon felt electrode and the proton membrane are Nafion 212 membrane. At a higher current density of 80 mA / cm 2 Charged to 1.0V at a higher current density of 80mA / cm 2 Discharge to 0.01V.
[0048] The assembled iron-based flow battery was subjected to 70 charge and discharge cycle tests. The charge and discharge efficiency and capacity-cycle curves within 70 cycles are shown in Figure 2. Figure 5 shown.
[0049] The coulombic efficiency (CE) of 70 cycles is close to 100% within 70 cycles, the voltage efficiency (VE) and energy efficiency (EE) are around 70%, and the charge and discharge capacity is relatively stable.
[0050] Embodiment 3:
[0051] In this embodiment, the main components of the negative electrode electrolyte include: ferric sulfate, N-(2-hydroxyethyl) iminodiacetic acid as a complex, potassium carbonate as a supporting electrolyte, sodium chloride as an auxiliary electrolyte, and oxygen-free deionized water as a solvent. Among them, the concentration of ferric sulfate is 0.2 mol / L, the concentration of N-(2-hydroxyethyl) iminodiacetic acid is 0.8 mol / L, the concentration of potassium carbonate is 1.2 mol / L, and the concentration of sodium chloride is 0.2 mol / L.
[0052] The specific steps for preparing the negative electrode electrolyte are as follows:
[0053] Take 8.0g of ferrous sulfate, 14.2g of N-(2-hydroxyethyl)iminodiacetic acid and 1.2g of sodium chloride, put them into a reactor, add 16.6g of potassium carbonate, add oxygen-free deionized water, then stir for 6h, transfer to a 100mL volumetric flask after complete dissolution, make up to volume with oxygen-free deionized water at room temperature, and use it after standing for 24h.
[0054] The electrolyte of the positive electrode is mainly 0.5 mol / L lithium ferrocyanide and 0.5 mol / L lithium carbonate electrolyte.
[0055] After the battery system is assembled, other reference conditions are the same as those in Example 1. To prevent the active material from being deactivated and the alkaline electrolyte from deteriorating, wait until the inert gas fills the entire battery system. Connect to the battery test system and start testing.
[0056] Connect to the battery test system and start the test. The volume of the positive and negative electrolytes is 25 ml each, and the positive and negative electrodes are 3×3 cm 2 The porous carbon felt electrode and the proton membrane are Nafion 212 membrane. At a higher current density of 80 mA / cm 2 The battery was charged to 0.9 V at a higher current density of 80 mA / cm 2 Discharge down to 0.01V.
[0057] The assembled iron-based flow battery was subjected to 90 charge and discharge cycle tests. The charge and discharge efficiency and capacity-cycle curves within 90 cycles are shown in Figure 2. Figure 6 shown.
[0058] The coulombic efficiency (CE) of the 90th cycle is close to 90%, the voltage efficiency (VE) decays from 70% in the first cycle to about 50%, and the energy efficiency (EE) decays from 60% in the first cycle to about 50%. The charge and discharge capacity tends to be stable after 30 cycles.
Claims
1. An iron-based liquid flow battery negative electrode electrolyte, characterized in that: The negative electrode electrolyte includes an active substance, a ligand, a supporting electrolyte, and an auxiliary electrolyte; the active substance is one or more of ferric sulfate, ferric nitrate, ferric chloride, and ferric acetate, and the ligand is one or more of tris(hydroxymethyl)methylglycine, N,N-bis(2-hydroxyethyl)glycine, and N-(2-hydroxyethyl)iminodiacetic acid.
2. The negative electrode electrolyte of an iron-based liquid flow battery according to claim 1, characterized in that: The supporting electrolyte is one or more of sodium hydroxide, potassium hydroxide, lithium hydroxide, potassium carbonate, sodium carbonate, and lithium carbonate; the auxiliary electrolyte is one or more of potassium chloride, potassium nitrate, sodium nitrate, sodium chloride, ammonium chloride, potassium sulfate, sodium sulfate, and ammonium sulfate; and the solvent is oxygen-free deionized water.
3. The negative electrode electrolyte of an iron-based liquid flow battery according to claim 1, characterized in that: When the ligand is tris(hydroxymethyl)methylglycine, the corresponding supporting electrolyte is one or more of sodium hydroxide, potassium hydroxide, and lithium hydroxide; when the ligand is N,N-bis(2-hydroxyethyl)glycine or / and N-(2-hydroxyethyl)iminodiacetic acid, the corresponding supporting electrolyte is one or more of potassium carbonate, sodium carbonate, and lithium carbonate.
4. The negative electrode electrolyte of an iron-based liquid flow battery according to claim 1, characterized in that: The molar ratio of the ligand to the iron ions in the active substance is 5:1 to 2:1, and the preferred ratio is 3:
1.
5. The negative electrode electrolyte of an iron-based liquid flow battery according to claim 1, characterized in that: The molar concentration of iron ions in the active substance is 0 to 1.2 mol / L and is not 0, preferably 0.1 to 0.6 mol / L; the molar concentration of the ligands tri(hydroxymethyl)methylglycine, N,N-bis(2-hydroxyethyl)glycine, and N-(2-hydroxyethyl)iminodiacetic acid is 0 to 5.0 mol / L and is not 0, preferably 0.5 to 2.5 mol / L; the molar concentration of the supporting electrolyte is 0 to 8.0 mol / L, preferably 1.0 to 4.0 mol / L; the molar concentration of the auxiliary electrolyte is 0 to 3.0 mol / L, preferably 0.2 to 1.5 mol / L.
6. A method for preparing a negative electrode electrolyte for an iron-based liquid flow battery according to any one of claims 1 to 5, characterized in that: The preparation process of the negative electrode electrolyte is as follows: (1) introducing an inert gas into the reactor to exhaust the air; (2) adding active substances, ligands, and auxiliary electrolytes, mixing, adding deionized water, and stirring for 1 to 3 hours; (3) Then add the supporting electrolyte and stir thoroughly for 1 to 3 hours to make a uniform solution.
7. An iron-based liquid flow battery, comprising a positive electrode, a negative electrode, positive and negative electrolytes, a diaphragm and a battery housing, wherein the positive electrode, the negative electrode, the positive and negative electrolytes and the diaphragm are contained in the battery housing, the diaphragm is located between adjacent positive and negative electrodes, and both sides of the diaphragm are in contact with the positive and negative electrolytes; characterized in that: The negative electrode electrolyte is an iron-based liquid flow battery negative electrode electrolyte as described in any one of claims 1-5.
8. An iron-based liquid flow battery according to claim 7, characterized in that: The positive electrode electrolyte is potassium ferrocyanide, an auxiliary electrolyte and / or a supporting electrolyte having the same anion as the supporting electrolyte of the corresponding negative electrode electrolyte.
9. An iron-based liquid flow battery according to claim 7, characterized in that: The positive electrode or negative electrode is a porous carbon material electrode; the corresponding diaphragm is a Nafion membrane with a thickness of 50 to 200 μm.
10. An iron-based liquid flow battery according to claim 7, characterized in that: The operating temperature of the negative electrode electrolyte is 10-70°C.
Citation Information
Patent Citations
Alkaline aqueous solution composition for treating a substrate
CN101717939A
High solubility iron hexacyanides
CN104755423A
Alkaline all-iron flow battery
CN112467179A
Electrolyte of water-based flow battery, all-iron water-based flow battery and application
CN113764714A
Liquid preparation and application thereof
CN116249552A